Service Learning in Cultural Preservation and Education in Kampung Glam Area, Singapore - Satriadi Satriadi; Ferry Siswadhi; Fitri Rezeki; Elondri Elondri; Andini Dwi Pratiwi; Nurul Rabbani (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Kampung Glam as a heritage area in Singapore faces modernization challenges that have the potential to shift local cultural identity. Service learning is applied to bridge cultural preservation efforts with community education through the collaboration of students, communities, and cultural stakeholders. The purpose of this activity is to strengthen cultural education, increase awareness of the younger generation, and support the sustainability of the creative economy based on local values. The methods used include needs mapping, collaborative solution design, implementation of cultural workshops, and sustainability evaluation. The results showed that students gained contextual experience on heritage management, while the local community was helped through educational materials, mentoring, and strengthening of cultural narratives. This activity also increases the understanding of the importance of a balance between the preservation of historical values and the development of the modern economy. In conclusion, service learning is effective as an educational approach and community empowerment in maintaining cultural identity. It is suggested that the program be continued with the development of cultural education modules and long-term partnerships to strengthen sustainability.